Countering commercial interests: building advocacy campaigns to protect children from food marketing - Wendy L Watson; Jane Martin (Sax Institute, 2019)
Objectives: To describe the strategies used by Cancer Council NSW (CCNSW) and Obesity Policy Coalition (OPC) to influence government policy on food marketing to children. Type of programs: Comprehensive advocacy campaigns. Methods: We present the components of an advocacy campaign run by OPC and another campaign run by CCNSW to protect children from unhealthy food marketing. We look at the successes and challenges of the campaigns and discuss future directions. Results: CCNSW has focused on a community-organising and mobilisation model, while OPC has invested in building relationships with key stakeholders such as decision makers. Both organisations have ensured that protecting children from unhealthy food marketing is highlighted through media advocacy and stakeholder engagement. The issue has remained a public health priority despite limited policy windows. Lessons learnt: Creating a climate for change and facilitating policy action to protect children from unhealthy food marketing can be achieved with: 1) presentation of a clear, united public-health solution; 2) using earned (or unpaid) media to gain public attention; and 3) sustained community and political engagement.